Microfluidic Mechanics and Applications: a Review - Sandeep Arya; Saleem Khan; Akhil Vaid; Harneet Kour; Parveen Lehana (Журнал нано- та електронної фізики)
Microfluidics involves the transportation, splitting and mixing of minute fluids to perform several chemical and biological reactions including drug screening, heating, cooling or dissolution of reagents. Efforts have been made to develop different microfluidic devices, droplets and valves that can stop and resume flow of liquids inside a microchannel. This paper provides the review related to the theory and mechanics of microfluidic devices and fluid flow. Different materials and techniques for fabricating microfluidic devices are discussed. Subsequently, the microfluidic components that are responsible for successful micrfluidic device formation are presented. Finally, recent applications related to the microfluidics are highlighted.